Pendidikan Islam Perspektif Buya Hamka di Era Digital - Silva, Alfi Dario; Muqit, Abd.; Hunaida, Wiwin Luqna (Lembaga Yasin AlSys, 2025)
The primary focus of this research is the imbalance between spiritual and material aspects in education, the impact of technology on Islamic education, and the challenges posed by anti-Islam ideologies in the digital era. The purpose of this study is to revitalize Buya Hamka's ideas on Islamic education, which can be applied to address contemporary issues. The research findings indicate that Buya Hamka's thoughts, particularly on independent thinking and the balance between intellectual, emotional, and spiritual aspects, remain relevant in shaping a morally upright younger generation capable of facing the challenges of the digital age. The study employs a library research method as its data source.